READING STRATEGIES USED BY STUDENTS OF DIFFERENT LEVELS OF ENGLISH READING PROFICIENCY - Bich Thuy, Nguyen Thi (VNU Journal of Foreign Studies, 2021)
Reading plays a vital role in academic development, particularly when learners have to work over a huge amount of foreign language materials for their own specialist subjects (McDonough & Shaw, 2013). Strengthening English reading ability is necessary for students to promote individual ability in university education. This study was conducted to explore if there were any differences in the use of reading strategies among university students of different levels of self-rated English reading proficiency. 957 students from 6 universities in the North of Vietnam participated in the study. The results of the study through the questionnaire adapted from Oxford’s (2013) Self-Strategic Regulation model (S2R) show that there were significant differences in the use of reading strategies among students of different self-rated levels of English reading proficiency, especially between students of good and poor proficiency. The highest frequencies in the use of each strategy category were in the group of self-rated good readers and the students of the poor group reported the lowest frequencies. The study also reveals individual strategies used the most and the least by each group of students.